2001
DOI: 10.1002/1438-9312(200102)103:2<93::aid-ejlt93>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phospholipid reverse micelles in relation to membrane processing of vegetable oils

Abstract: Studies were conducted to determine the critical micelle concentration (CMC) of phospholipids in vegetable oils and the size of reverse micelles to understand their rejection phenomenon in the membrane process. The CMC values of phosphatidylcholine (PC) in triolein and phospholipids in crude soybean oil were determined to be 440 and 1020 mg/kg, respectively, by using TCNQ (7,7,8,8-tetracyano-quinodimethane) solubilization technique. The surface tension measurements of these samples gave similar values of CMC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…It was reported that at the particular concentration of phosphatidylcholine (8,900 mg/kg), when the ratio of water to phosphatidylcholine was increased from 0.079 to 0.112, the size of micelles increased from 3.56 to 4.60 nm (Subramanian et al . ). Subramanian et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was reported that at the particular concentration of phosphatidylcholine (8,900 mg/kg), when the ratio of water to phosphatidylcholine was increased from 0.079 to 0.112, the size of micelles increased from 3.56 to 4.60 nm (Subramanian et al . ). Subramanian et al .…”
Section: Resultsmentioning
confidence: 97%
“…However, there have been few attempts focusing on enhancing reverse micelle content as well as hydratable PLs to improve the performance of oil refining by membranes (Subramanian et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…A meniscus is formed between the wet and solid surface due to surface tension that reduces the pressure of the liquid, causing an attractive force (Ranade 1987). Addition of lecithin to oil lowers its surface tension (Subramanian et al. 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The conventional oil refinement process is characterized by high energy, water, and chemical product requirements, loss in neutral oil and nutrients, and a high rate of effluent production (Subramanian et al, 2001;Roy et al, 2014). In contrast, the use of membranes during processing has been shown to simplify the process.…”
Section: Introductionmentioning
confidence: 99%